Metre and Stress in Old Khotanese - Sims-Williams, Nicholas (Indo-Iranian journal, 2025)
In Sims-Williams 2022 I argued that the metre of the Old Khotanese Book of Zambasta combines quantitative and accentual principles. This conclusion has been disputed by Marco Fattori (2025), who claims that Old Khotanese metre is exclusively quantitative. In the present article I attempt to re-establish the role of stress, showing that Fattori’s analysis is unduly abstract and fails to account for significant features of the metrical system.